2022
DOI: 10.1108/pm-07-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Constructing segmented rental housing indices: evidence from Beijing, China

Abstract: PurposeThis paper aims to construct rental housing indices and identify market segmentation for more effective property-management strategies.Design/methodology/approachThe hedonic model was employed to construct the rental indices. Using the k-means++ and REDCAP (Regionalisation with Dynamically Constrained Agglomerative Clustering and Partitioning) approaches, the authors conducted clustering analysis and identified different market segmentation. The empirical study relied on the database of 80,212 actual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…We apply Ordinary Least Squares (OLSs) regression to estimate the following empirical model (1). OLS regression is commonly used in the property research to examine the relationship between variables in the cross-sectional setting (e.g., Donner and Loh, 2019; Sharma, 2022; Song et al ., 2022).…”
Section: Data Variables and Estimation Methodsmentioning
confidence: 99%
“…We apply Ordinary Least Squares (OLSs) regression to estimate the following empirical model (1). OLS regression is commonly used in the property research to examine the relationship between variables in the cross-sectional setting (e.g., Donner and Loh, 2019; Sharma, 2022; Song et al ., 2022).…”
Section: Data Variables and Estimation Methodsmentioning
confidence: 99%
“…There are a number of empirical studies with a focus on the spatial effects that influence the house price index, some of which advocate for the consideration of spatial models over OLS models in estimating the house prices (Peng, 2020). Song et al (2022) implicitly support the view that spatial regression models improve the multiple regression real estate models that suffer from heterogeneity. Furthermore, Brunes et al (2020) observed that the spatial hedonic model was superior to the classical OLS hedonic model, which ignores spatial effects, and that the OLS model exaggerated the parameter estimates.…”
Section: House Price Indexmentioning
confidence: 99%
“…This has facilitated the availability of crucial market information to stakeholders such as planners and property developers and other policy makers in the property industry (Hacievliyagil et al , 2022). Many of these studies have taken into account proximity and spatial effects (Song et al , 2022; Peng, 2020; Sipan et al , 2018). This is because house prices usually have a relationship to spatial issues (Ismail et al , 2021).…”
Section: Introductionmentioning
confidence: 99%